Role of inhibin and activin in the modulation of gonadotropin- and steroid-induced oocyte maturation in the teleost Fundulus heteroclitus - Toussaint Gesulla; Petrino Teresa R; Lin Yu-Wai P (BMC, 2007)
Abstract Background Activin and inhibin are glycoproteins structurally related to the transforming growth factor-beta superfamily. These peptides were first described as factors that regulate the follicle-stimulating hormone (FSH) at the pituitary level. The possible role of inhibin and activin, at the ovarian level, in mediating the stimulatory actions of a Fundulus pituitary extract (FPE) and 17alpha,20beta-dihydroprogesterone (DHP) on oocyte maturation was investigated in this study. Methods In vitro culture of ovarian follicles and induction of oocyte maturation were carried out in 75% Leibovitz L-15 medium. Follicles or denuded oocytes were exposed to FPE, inhibin, activin, ethanol vehicle (control group), or DHP. The competence of the follicles or denuded oocytes to respond to the hormones was assessed by scoring germinal vesicle breakdown (GVBD) used as an indication of the reinitiation of meiosis or oocyte maturation. DHP level was measured by radioimmunoassay. Results Addition of FPE promoted the synthesis of DHP by the granulose cells of fully grown ovarian follicles and thus stimulated GVBD in the oocyte. Presence of porcine inhibin did not hinder the synthesis of DHP stimulated by FPE, although it did inhibit the subsequent GVBD in a dose-dependent manner, suggesting that the action of inhibin was at the oocyte level. Similarly to the findings with FPE, inhibin also blocked the DHP-induced GVBD in intact follicles, as well as the spontaneous and steroid-induced GVBD of denuded oocyte. Inhibin straightforwardly blocked the response to a low dose of DHP throughout the culture period, while higher doses of the steroid appeared to overcome the inhibitory effect especially at later times. In contrast to inhibin, recombinant human activin A significantly enhanced DHP-induced GVBD in a dose-dependent manner after 48 hr, although activin alone was not able to induce GVBD without the presence of the steroid. Conclusion Taking together with our previous studies that demonstrate the presence of activin/inhibin subunits in the ovary of F. heteroclitus, these in vitro findings indicate that inhibin and activin are local regulators in the teleost ovary and have opposing effects in modulating oocyte maturation.